Bioluminescent Imaging of Pneumococcal Otitis Media in Chinchillas. (May 2013) - Johnson, Alan W.; Sidman, James D.; Lin, Jizhen
Objectives: Bioluminescent imaging has emerged as a powerful tool for monitoring the pathological process of infections in animals. The purpose of this study was to harness this new tool for objective assessment of acute otitis media (AOM) in animals with and without antibiotic interventions. Methods: Thirty-six healthy chinchillas, free of middle ear infections, were randomly divided into a control group and a group that received amoxicillin treatment. Bioluminescent Streptococcus pneumoniae (Xen 10) was injected into the epitympanic bullae of chinchillas (50 colony-forming units each) for induction of AOM. The infectious process of Xen 10 in the bullae of living animals with and without antibiotic interventions was monitored in real time with bioluminescence equipment. Results: A dynamic change of bioluminescent signals in the bullae of chinchillas from days 1 to 14 was observed after Xen 10 injection. Amoxicillin treatment reduced the bioluminescent signals in the bullae of chinchillas compared with controls. The AOM persisted for 14 days, and middle ear effusion for 6 weeks, in the control animals, whereas AOM lasted for 2 days, and effusion for 6 to 12 days, in the antibiotic-treated animals. Conclusions: Bioluminescent imaging provides an innovative method for assessment of the bacterial loads in the middle ear of chinchillas in a real-time manner and is very useful for objective evaluation of the efficacy of therapeutic interventions.